Ensuring the Stability of the Genome: DNA Damage Checkpoints - Christine Latif; Susan H. Harvey; Susan J. O'Connell (The Scientific World Journal)
The cellular response to DNA damage is vital for the cells ability to maintain genomic integrity. Checkpoint signalling pathways, which induce a cell cycle arrest in response to DNA damage, are an essential component of this process. This is reflected by the functional conservation of these pathways in all eukaryotes from yeast to mammalian cells. This review will examine the cellular response to DNA damage throughout the cell cycle. A key component of the DNA damage response is checkpoint signalling, which monitors the state of the genome prior to DNA replication (G1/S) and chromosome segregation (G2/M). Checkpoint signalling in model systems including mice, Xenopus laevis, Drosophila melanogaster, and the yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe have been useful in elucidating these pathways in mammalian cells. An examination of this research, with emphasis on the function of checkpoint proteins, their relationship to DNA repair, and their involvement in oncogenesis is undertaken here.